Sweden : 2010 Article IV Consultation; Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Sweden. (IMF Staff Country Reports; Country Report, 2010)
Sweden was among the first to falter in the great recession. The downturn was mitigated by aggressive stabilization policies, led by a sharp relaxation of monetary policy, a slew of emergency financial sector support measures, and actions raising bank capital. The policy actions taken were effective because they occurred against the background of Sweden's credible inflation targeting, freely floating exchange rate, and budgetary frameworks. The intention to keep policies supportive are appropriate. Fiscal policy anchors this effort, and the monetary stance is highly accommodative.